Performance testing and comparing between conventional and metamaterial rectangular patch antenna / Khairul Ikmar Jamaludin - Jamaludin, Khairul Ikmar (2014)
This thesis presents the performance testing of both rectangular conventional and metamaterial patch antenna with electromagnetic bandgap structure (EBG) approach on the ground plane. The performances of both antennas are compared to determine which one had the better performance as a receiver with fixed transmitter. Both antennas operate at the same frequency of 2.4GHz. The scope of performance testing includes the signal strength and the transfer duration of two files which differ in size (16.6MB and 369MB). The testing was done by using two Ubiquiti equipments which is Bullet M2 as a transceiver embedded with AirOS firmware for the test bed. The transceivers are connected to the laptops for configuring and monitoring. The scope of projects includes varying output power for the transmitter and the distance between transmitter and receiver. Table and graph of the results obtained are tabulated. From the results, it is proven that conventional patch antenna is better as receiving antenna since it has better signal strength of -70dBm compared to the metamaterial patch antenna which only recordedto have -74dBm at the 20 metres distance between transmitter and receiver. On top of that, the average time taken to complete file transfer also shows that the conventional antenna has better performance compared to metamaterial patch antenna with the duration of24.44 seconds (16.6MB file) and i51.44 seconds (369MB file) while the metamaterial is having longer duration to complete transferring file with 51.21 seconds (16.6MB file) and 236.5 seconds (369MB file).